Neutrophils in asthma: the good, the bad and the bacteria. - Crisford, Helena; Sapey, Elizabeth; Rogers, Geraint B; Taylor, Steven; Nagakumar, Prasad; Lokwani, Ravi; Simpson, Jodie L (Thorax, 2021)
Airway inflammation plays a key role in asthma pathogenesis but is heterogeneous in nature. There has been significant scientific discovery with regard to type 2-driven, eosinophil-dominated asthma, with effective therapies ranging from inhaled corticosteroids to novel biologics. However, studies suggest that approximately 1 in 5 adults with asthma have an increased proportion of neutrophils in their airways. These patients tend to be older, have potentially pathogenic airway bacteria and do not respond well to classical therapies. Currently, there are no specific therapeutic options for these patients, such as neutrophil-targeting biologics.Neutrophils comprise 70% of the total circulatory white cells and play a critical defence role during inflammatory and infective challenges. This makes them a problematic target for therapeutics. Furthermore, neutrophil functions change with age, with reduced microbial killing, increased reactive oxygen species release and reduced production of extracellular traps with advancing age. Therefore, different therapeutic strategies may be required for different age groups of patients.The pathogenesis of neutrophil-dominated airway inflammation in adults with asthma may reflect a counterproductive response to the defective neutrophil microbial killing seen with age, resulting in bystander damage to host airway cells and subsequent mucus hypersecretion and airway remodelling. However, in children with asthma, neutrophils are less associated with adverse features of disease, and it is possible that in children, neutrophils are less pathogenic.In this review, we explore the mechanisms of neutrophil recruitment, changes in cellular function across the life course and the implications this may have for asthma management now and in the future. We also describe the prevalence of neutrophilic asthma globally, with a focus on First Nations people of Australia, New Zealand and North America.